Influence of Using Microbial Transglutaminase on the Physicochemical Properties, Volatile Compounds and Free Amino Acid Composition of Pastırma - Suncak, Fatma Yağmur Hazar; Kaban, Güzin; Kaya, Mükerrem (MDPI AG, 2025)
The effects of different levels of microbial transglutaminase (MTGase) at 0% (control), 0.25%, 0.50% and 1% on the physicochemical properties, volatile compounds and free amino acid composition of pastırma, a Turkish dry-cured meat product, were investigated. The MTGase treatment had no significant effect on the aw, L* and b* values of pastırma. The thiobarbituric acid reactive substances value decreased as the MTGase level increased. The maximum cutting force was found to be higher in enzyme-treated pastırma groups compared with the control. Enzyme treatment increased the maximum stress–relaxation force, but no statistical difference was observed between the 0.50% and 1% enzyme treatments. No significant differences were observed between groups in the volatile compound profile. However, in the correlation analysis, the control group showed a close correlation with the 0.25% MTGase group. This was also the case for the 0.5% and 1% MTGase groups. In the samples, glutamic acid, arginine, alanine, cystine and valine were determined to be the dominant free amino acids, and glutamic acid showed a close correlation with valine; lysine with arginine; and cystine with serine. MTGase had no significant effect on the total free amino acid content.
Keywords: Technology; QH301-705.5; T; Physics; QC1-999; Engineering (General). Civil engineering (General); pastırma; transglutaminase; Chemistry; free amino acid composition; TA1-2040; Biology (General); cured meat product; volatile compound; QD1-999